THE SOBO PENDOPO DIALOGUE: Manifestation of Deliberation Democracy in Bojonegoro District - Galang Geraldy (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
The background of complex socio-economic issues became the lighter of the political revolution of openness and deliberation in Bojonegoro district. The Sobo Pendopo Dialogue, initiated since the election of Kang Yoto-Kang Hartono in the 2008 election, is the start to disseminating the practice of the political revolution of openness. On that basis, the consistency of local democratization during one windu brings world appreciation through Open Government Partnership 2016. Dialogue Sobo Pendopo, in a dialectical discourse of liberal and substantial democracy, breaks down liberal assumptions that include economic and social capital as a prerequisite to the nature of democracy. Departure from that, Dialog Sobo Pendopo in the analysis through exploration theory of deliberation democracy. The concept of political participation, public space and civil society becomes the blueprint for the deliberation context of democracy in Dialog Sobo Pendopo. The research method is qualitative with grounded theory type. The presence of Sobo Dialogue Pendopo which enhances the development of the degree of local democracy, the researchers believe that the public space can transform into a public body, where the institutionalization of civic politics legitimacy really becomes the main base in strengthening the role of civil society.Latar belakang persoalan sosial ekonomi yang kompleks menjadi pemantik revolusi politik keterbukaan dan deliberasi di Kabupaten Bojonegoro. Dialog Sobo Pendopo, yang digagas sejak ketepilihan Kang Yoto-Kang Hartono dalam pilkada tahun 2008 ini, menjadi pintu dalam mendiseminasi praktik revolusi politik keterbukaan. Atas dasar itu, konsistensi demokratisasi lokal selama satu windu membawa apresiasi dunia melalui Open Government Partnership 2016. Dialog Sobo Pendopo, secara dialektika wacana demokrasi liberal dan substansial, mematahkan asumsi-asumsi liberal yang menyertakan modal ekonomi dan sosial sebagai prasyarat menuju hakikat demokrasi. Berangkat dari hal tersebut, Dialog Sobo Pendopo di analisa melalui eksplorasi teori demokrasi deliberative yang diinterpretasi konsep partisipasi politik, ruang publik dan civil society. Metode penelitian adalah kualitatif dengan tipe grounded theory. Kehadiran Dialog Sobo Pendopo yang meningkatkan perkembangan derajat demokrasi lokal, peneliti meyakini ruang publik tersebut dapat bertransformasi menjadi badan publik, dimana kelembagaan legitimasi politik kewargaan benar-benar menjadi basis utama dalam memperkuat peranan civil society.Keyword: The Sobo Pendopo Dialogue, Deliberation Democracy, Bojonegoro District